Policy analysis of national health financing implementation on access and equity of healthcare services in rural communities - Suprapto Suprapto (JAKESPOL Journal of Health Policy Analysis, 2026)
Introduction: Healthcare inequities remain common in rural communities despite national health financing programs designed to achieve universal health coverage. Geographic barriers, limited healthcare services, and administrative challenges continue to affect healthcare accessibility. Methods: A quantitative cross-sectional study was conducted in rural districts of Eastern Indonesia from January to April 2026 involving 348 respondents selected through multistage cluster sampling. Data were analyzed using chi-square tests and multivariate logistic regression with adjusted odds ratios (AOR) and 95% confidence intervals (CI). Results: More than half of respondents (56.9%) experienced healthcare access difficulties despite active insurance enrollment. Limited healthcare service availability was the strongest predictor of healthcare barriers (AOR = 3.46; 95% CI: 2.01–5.95; p < 0.001). Geographic distance, low income, transportation problems, and administrative complexity were also significantly associated with healthcare inequities. Conclusion: National health financing policies have improved financial coverage but remain insufficient to eliminate rural healthcare disparities. Strengthening healthcare infrastructure, transportation systems, and governance mechanisms is necessary to improve equitable healthcare access.